Developing e-government policy through social media platform in Makassar city, Indonesia - Yusmanizar, Yusmanizar; Djalil, Nur Alim; Yulhaidir, Yulhaidir; Alyas, Alyas (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
Social media as a tools of e-government implementation, several of studied show that by using social media is significantly able to change the interaction between the government and citizens. The interaction increase administrative transparency and encourage citizens to collaborate in development agenda setting, facilitate mobilization for strengthening public policies, and facilitate public services produced jointly between citizens and the government. The citizens have ownership and to participate in maintaining the government policies. This study aims to describe the policy of the government in Makassar City, and development of e-government using social media which is based on the weak phenomenon of e-government development in Makassar City, particularly with the smart city plan since 2014. The method used is an assessment of the use of official social media platforms and e-government development policies in Makassar City. The research locus is the Makassar City Communication and Information Office, which is the center for disseminating official information of the Makassar City Government. The results showed that the development of e-government in Makassar City is still very limited, in terms of regulation there is no support for institutional strengthening of e-government, no e-government master plan as an implementation guideline and no e-government application system blue print, as a basis or standard for application development to achieve an integrated platform.